One-Pot Synthesis of Novel Furochromone and Oxazocine Derivatives as Promising Antitumor Agents with Their Molecular Docking Studies - Rita M. Borik (Journal of Chemistry)
One-pot efficient synthesis of novel chromone derivatives 4a–h and that of 5a–h were described in a simple method via four-component reaction between furochromone carbaldehyde, amine, isocyanate derivatives, and benzoic acid derivatives or nicotinic acid, respectively. Also, oxazocine derivatives 7a, b were prepared via reaction of visnagine carbaldehyde, ethyl acetoacetate and isocyanate derivatives 2a, b. The obtained derivatives of novel furochromone and oxazocine derivatives were evaluated as promising antitumor agents against panel of two human cell lines, hepatocellular carcinoma (HEPG2) and breast carcinoma (MCF7). The antitumor results suggested that furochromone derivatives 5a–h have activity against MCF7 in comparison with doxorubicin as the standard drug. Furthermore, the molecular docking studies of these novel derivatives of furochromone and oxazocine showed good agreement with the biological results when their binding pattern and affinity towards the active site of EGFR was investigate.